2-Year Clinical Outcomes of an Abluminal Groove–Filled Biodegradable-Polymer Sirolimus-Eluting Stent Compared With a Durable-Polymer Everolimus-Eluting Stent - Xu, Bo; Saito, Yuichi; Baumbach, Andreas; Kelbæk, Henning; van Royen, Niels; Zheng, Ming; Morel, Marie Angèle; Knaapen, Paul; Slagboom, Ton; Johnson, Thomas W.; Vlachojannis, Georgios; Arkenbout, Karin E.; et al. (Jacc-Cardiovascular Interventions, 2019)
Objectives: The aim of this study was to assess the 2-year clinical outcomes of the Firehawk stent (Shanghai MicroPort Medical Group, Shanghai, China), a novel abluminal groove–filled biodegradable-polymer sirolimus-eluting coronary stent, compared with XIENCE (Abbott Vascular, Santa Clara, California), a durable-polymer everolimus-eluting coronary stent. Background: The long-term outcomes of the Firehawk stent have not been evaluated beyond 1 year in a randomized all-comers clinical trial. Methods: The TARGET All Comers study is a prospective, multicenter, all-comers, randomized, noninferiority trial conducted in Europe. A total of 1,653 patients were randomly assigned to undergo implantation of either the Firehawk or the XIENCE stent. The primary endpoint was target lesion failure, a composite of cardiac death, target vessel myocardial infarction, or ischemia-driven target lesion revascularization. Results: At 2-year follow-up, the incidence of target lesion failure was 8.7% in the Firehawk group versus 8.6% in the XIENCE group (p = 0.92). The event rates of individual components of the primary endpoint were comparable for the 2 groups. Landmark analyses between 1- and 2-year follow-up revealed no statistically significant difference of TLF for the Firehawk versus the XIENCE stent. Beyond 1 year, very late definite or probable stent thrombosis occurred in 3 patients (0.4%) in the Firehawk group and in 7 patients (0.9%) in the XIENCE group (p = 0.34). Conclusions: The 2-year follow-up of the TARGET All Comers study confirms comparable safety and efficacy profiles of the Firehawk and XIENCE stents.
CRIS-Team Scopus Importer:2019-09-03
Keywords: clinical outcome; drug-eluting stent; everolimus-eluting stent; Firehawk

3D imaging of myocardial perfusion and coronary tree morphology from a single rotational angiogram - Lauritsch, Günter; Rohkohl, Christopher; Hornegger, Joachim; Sinha, Anil-Martin; Rittger, Harald; Brachmann, Johannes; Rieber, Johannes; Rittger, Harald (Medical Imaging 2011: Visualization, Image-Guided Procedures, and Modeling, 2011)
Diagnosis and treatment of coronary heart disease are performed in the catheter laboratory using an angiographic X-ray C-arm system. The morphology of the coronary tree and potentially ischemic lesions are determined in 2D projection views. The hemodynamic impact of the lesion would be valuable information for treatment decision. Using other modalities for functional imaging is disrupting the clinical workflow since the patient has to be transferred from the catheter laboratory to another scanner, and back to the catheter laboratory for performing the treatment. In this work a novel technology is used for simultaneous 3D imaging of first pass perfusion and the morphology of the coronary tree from a single rotational angiogram. A selective, single shot of contrast agent of less than 20ml directly into the coronaries is sufficient for a proper contrast resolution. Due to the long acquisition time cardiac motion has to be considered. A novel reconstruction technique for estimation and compensation of cardiac motion from the acquired projection data is used. The overlay of the 3D structure of the coronary tree and the perfusion image shows the correlation of myocardial areas and the associated coronary sections supporting that region. In a case example scar lesions caused by a former myocardial infarct are investigated. A first pass perfusion defect is found which is validated by a late enhancement magnetic resonance image. No ischemic defects are found. The non vital regions are still supported by the coronary vasculature. © 2011 SPIE.

A 3-Hour Diagnostic Algorithm for Non-ST-Elevation Myocardial Infarction Using High-Sensitivity Cardiac Troponin T in Unselected Older Patients Presenting to the Emergency Department - Bahrmann, Philipp; Christ, Michael; Bahrmann, Anke; Rittger, Harald; Heppner, Hans Jürgen; Achenbach, Stephan; Bertsch, Thomas; Sieber, Cornel (Journal of the American Medical Directors Association, 2013)
Objectives: To determine if an algorithm implementing a serial high-sensitive cardiac troponin T (hs-cTnT) measurement at presentation (0h) and at 3 hours after presentation (3h) is helpful for early diagnosis of non-ST-elevation myocardial infarction (NSTEMI) in older patients.Design: Prospective observational cohort study.Setting: An emergency department (ED) of a city hospital covering a population of approximately 1 million in Germany.Participants: A total of 332 consecutive unselected patients were recruited, of whom 25 had one or more of the prespecified exclusion criteria and 1 had a missing hs-cTnT at 3h, resulting in a final population of 306 patients.Measurements: In addition to clinical examination, hs-cTnT was measured at 0h and 3h. The final diagnosis of NSTEMI was adjudicated by two independent consultants and an algorithm for rule-in and rule-out of NSTEMI was developed using classification and regression tree analysis. All patients were followed-up for cardiovascular outcome within 12 months.Results: Among 306 patients (mean age 81 +/- 6 years), 38 (12%) patients had NSTEMI. Accuracy to diagnose NSTEMI was significantly higher for hs-cTnT measurements at 3h versus 0h (area under the receiver operating characteristic curve [AUC] 0.88 vs. 0.82, P = .0038) and for absolute versus relative hs-cTnT delta changes (AUC 0.89 versus 0.69, P < .001). A diagnostic algorithm using hs-cTnT values at presentation and absolute delta changes values ruled-in NSTEMI in 23% and ruled-out NSTEMI in 35% of patients. For patients neither fulfilling the rule-in nor the rule-out criteria, an observational zone was established. Cumulative 1-year survival was 79.4%, 88.5%, and 99.1% in patients classified as rule-in, observational zone, and rule-out, respectively.Conclusion: In older patients, serial hs-cTnT measurements and absolute delta-changes at 3h were valuable for early diagnosis of NSTEMI. An algorithm ruled-in NSTEMI in one quarter of patients with high risk and ruled-out NSTEMI in one-third with low risk. Copyright (c) 2013 - American Medical Directors Association, Inc.
Keywords: Troponin; aged; emergencies; myocardial infarction; decision support techniques

Angiographic patterns of drug-eluting stent restenosis after treatment with drug-coated balloon versus balloon angioplasty: Late lumen loss subgroup analyses of the PEPCAD-DES study - Rittger, Harald; Woehrle, Jochen; Brachmann, Johannes; Hohenforst-Schmidt, Wolfgang; Schlundt, Christian; Lonke, Sandra; Von Cranach, Moritz; Markovic, Sinisa; Achenbach, Stephan; Waliszewski, Matthias (Catheterization and Cardiovascular Interventions, 2016)
OBJECTIVES: This report provides the results of additional late lumen loss (LLL) analyses the predefined subgroup of diabetics and post hoc analyses of selected lesion morphologies to further elucidate the efficacy of paclitaxel coated balloon (PCB) angioplasty (clinical trials identifier NCT00998439). BACKGROUND: The PEPCAD-DES trial revealed that in lesion LLL and the target lesion revascularization rate (TLR) were significantly reduced with PCB angioplasty as compared with plain old balloon angioplasty (POBA) in patients with drug-eluting stent restenosis (DES-ISR). METHODS: A total of 110 patients with restenosis of Sirolimus- (SES), Everolimus- (EES), or Paclitaxel-eluting (PES) stents in native coronary arteries were randomized 2:1 to receive treatment with PCB (72 patients) or POBA (38 patients). RESULTS: In the PCB group, LLL did not differ for PES versus non-PES lesions (0.46 ± 0.55 mm vs. 0.41 ± 0.65 mm, P = 0.81). Moreover, there was no difference in LLL when PCB's were used in single and multiple layer DES-ISR (0.35 ± 0.60 mm vs. 0.51 ± 0.63 mm, P = 0.31). In contrast, patients treated with POBA for multilayer DES-ISR were more likely to have significantly higher LLL as compared with single layer DES-ISR (1.29 ± 0.76 mm vs. 0.65 ± 0.60 mm, P = 0.02). There was no LLL difference between diabetics and non-diabetics when treated with PCB angioplasty (0.46 ± 0.76 mm vs. 0.43 ± 0.54 mm, P = 0.83). CONCLUSION: Our hypothesis generating results indicated that there were no differences in terms of LLL when PCB angioplasty was applied in subgroups of single versus multiple layer DES-ISR and PES-ISR versus non-PES ISR. LLL was not higher in diabetic patients as compared with the their non-diabetic counterparts when treated with PCB's. © 2016 Wiley Periodicals, Inc.
EVALuna2:33671

Arbeitsanweisung in Herzkatheterlabor und Hybridoperationssaal - Schächinger, V.; Nef, H.; Achenbach, Susanne; Butter, C.; Deisenhofer, I.; Eckardt, L.; Eggebrecht, H.; Kuon, E.; Levenson, B.; Linke, A.; Madlener, K.; Mudra, H.; et al. (Der Kardiologe, 2015)
According to the German Radiation Act §18 (2) (Röntgenverordnung) every radiation facility administering radiation to humans has to provide written working instructions for those examinations and treatment procedures which are frequently performed. This is also valid for catheterization laboratories and hybrid operating rooms. It is the duty of the radiation protection officer (Strahlenschutzbeauftragte), a person who has to be appointed by German law (§15 Abs. 2 Nr. 1 Röntgenverordnung) to formulate and implement the working instructions. The current manuscript is a template to create such working instructions, which fulfill the legal requirements.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac catheterization; Hybrid operating room; Radiation act; Radiation protection; Work instruction

Comparison of Exo-Seal(®) and Angio-Seal (®) for arterial puncture site closure: A randomized, multicenter, single-blind trial - Ketterle, Johannes; Rittger, Harald; Helmig, Inga; Klinghammer, Lutz; Zimmermann, Stefan; Hohenforst-Schmidt, Wolfgang; Brachmann, Johannes; Nef, Holger; Achenbach, Stephan; Schlundt, Christian (Herz, 2015)
The use of extravascular femoral closure devices in patients undergoing coronary angiography/intervention has not been sufficiently evaluated. We sought to define the impact of an extravascular polyglycolic acid (PGA) plug for the closure of a femoral access site in patients undergoing coronary angiography and/or percutaneous coronary intervention.In this prospective, single-blind, multicenter trial we randomly assigned 319 patients to vessel closure with Angio-Seal(®) or Exo-Seal(®). We hypothesized that the use of an extravascular closure device is not inferior to an anchor/plug-mediated device regarding the occurrence of the composite primary endpoint: hematoma > 5 cm, significant groin bleeding (TIMI major bleed), false aneurysm, and device failure.There was no significant difference in patient baseline characteristics or procedural results. After 24 h the primary endpoint occurred in nine patients (5.6 %) in the Angio-Seal(®) group and in 13 patients (8.2 %) inthe Exo-Seal(®) group (p = 0.38). Hematoma > 5 cm was noted in three patients (1.9 %) receiving Angio-Seal(®) vs. two patients (1.3 %) receiving Exo-Seal(®) (p = 0.99). In one patient (0.6 %) of the Exo-Seal(®) group, TIMI major bleeding occurred, requiring transfusion (p = 0.49). There were four (2.5 %) false aneurysms found in patients treated with Angio-Seal(®) and two (1.3 %) in patients treated with Exo-Seal(®) (p = 0.68). There was a trend for a higher incidence of device failure in the Exo-Seal(®) group (1.2 vs. 5.2 %, p = 0.06). At telephone interview after 30 days, there was no significant difference found regarding the events readmission with surgery of puncture site, infection, bleeding, hematoma, or pain.In the present study, there were no significant differences found regarding the occurrence of hematoma > 5 cm, major bleeding, false aneurysm, and device failure between Angio-Seal(®) and Exo-Seal(®) 24 h after device implantation.
EVALuna2:12086

Comparison of intracoronary versus intravenous administration of adenosine for measurement of coronary fractional flow reserve - Schlundt, Christian; Bietau, Christian; Klinghammer, Lutz; Wiedemann, Ricarda; Rittger, Harald; Ludwig, Josef; Achenbach, Stephan (Circulation: Cardiovascular Interventions, 2015)
Measurement of fractional flow reserve (FFR) constitutes the current gold standard to evaluate the hemodynamic significance of coronary stenoses. Limited data validate the intracoronary application of adenosine against standard intravenous infusion. We systematically compared FFR measurements during intracoronary and intravenous application of adenosine about agreement and reproducibility.We included 114 patients with an intermediate degree of stenosis in coronary angiography. Two FFR measurements were performed during intracoronary bolus injection (40 ?g for the right and 80 ?g for the left coronary artery, FFRic), and 2 FFR measurements during continuous intravenous infusion of adenosine (140 ?g/kg per minute, FFRiv). FFR value, the time to reach FFR and patient discomfort (on a subjective scale from 0 for no symptoms to 5 for maximal discomfort) were recorded for each measurement. Mean time to FFR was 100 ± 27 s for continuous intravenous infusion versus 23 ± 14 s for intracoronary bolus administration of adenosine (P < 0.001). Reported discomfort after intracoronary application was significantly lower compared with intravenous adenosine (subjective scale > 0 in 35.1% versus 87.7% of the patients; P < 0.001). Correlation between FFRiv and FFRic was extremely close (r = 0.99; P < 0.001) with no systematic bias in Bland-Altman analysis (bias 0.002 [confidence interval, -0.001 to 0.005]) and low intermethod variability (1.56%). Intramethod variability was not different between intravenous and intracoronary administration (1.47% versus 1.33%; P=0.5).Intracoronary bolus injection of adenosine (40 ?g for the right and 80 ?g for the left coronary artery) yields identical FFR results compared with intravenous infusion (140 ?g/kg per minute), while requiring less time and offering superior patient comfort.
EVALuna2:12052

Crystalline sirolimus-coated balloon (cSCB) angioplasty in an all-comers, patient population with stable and unstable coronary artery disease including chronic total occlusions: rationale, methodology and design of the SCORE trial - Otto, Sylvia; Diaz, Victor Alfonso Jimenez; Weilenmann, Daniel; Cuculi, Florim; Nuruddin, Amin Ariff; Leibundgut, Gregor; Alfonso, Fernando; Wan Ahmad, Wan Azman; Pyxaras, Stylianos; Rittger, Harald; Steen, Philip; Gaede, Luise; et al. (Bmc Cardiovascular Disorders, 2023)
BackgroundA decade ago, the iopromide-paclitaxel coated balloon (iPCB) was added to the cardiologist's toolbox to initially treat in-stent restenosis followed by the treatment of de novo coronary lesions. In the meantime, DES technologies have been substantially improved to address in-stent restenosis and thrombosis, and shortened anti-platelet therapy. Recently, sirolimus-coated balloon catheters (SCB) have emerged to provide an alternative drug to combat restenosis.MethodsThe objective of this study is to determine the safety and efficacy of a novel crystalline sirolimus-coated balloon (cSCB) technology in an unselective, international, large-scale patient population. Percutaneous coronary interventions of native stenosis, in-stent stenosis, and chronic total occlusions with the SCB in patients with stable coronary artery disease or acute coronary syndrome were included. The primary outcome variable is the target lesion failure (TLF) rate at 12 months, defined as the composite rate of target vessel myocardial infarction (TV-MI), cardiac death or ischemia-driven target lesion revascularization (TLR). The secondary outcome variables include TLF at 24 months, ischemia driven TLR at 12 and 24 months and all-cause death, cardiac death at 12 and 24 months.DiscussionSince there is a wealth of patient-based all-comers data for iPCB available for this study, a propensity-score matched analysis is planned to compare cSCB and iPCB for the treatment of de novo and different types of ISR. In addition, pre-specified analyses in challenging lesion subsets such as chronic total occlusions will provide evidence whether the two balloon coating technologies differ in their clinical benefit for the patient.
CRIS-Team WoS Importer:2023-04-21

Drug-coated balloons in the treatment of small vessel disease - Rittger, Harald; Scheller, Bruno (Heart, 2014)
EVALuna2:12012

Fast-track high-sensitive cardiac troponin T algorithm for diagnosis of non-ST-elevation myocardial infarction in older patients at the emergency department - Bahrmann, Philipp; Christ, M.; Bahrmann, A.; Rittger, Harald; Achenbach, Stephan; Bertsch, T.; Sieber, Cornel; Heppner, Hans Jürgen (European Heart Journal, 2013)

His bundle pacing guided by automated intrinsic morphology matching is feasible in patients with narrow QRS complexes - Bastian, Dirk; Gregorio, Caterina; Buia, Veronica; Walaschek, Janusch; Rittger, Harald; Vitali-Serdoz, Laura (Scientific Reports, 2022)
Pace mapping and visual comparison of the local pacing response with the intrinsic QRS morphology form the mainstay of His bundle pacing (HBP). We evaluated the performance of a surface lead morphology match algorithm for automated classification of the pacing response in patients with narrow intrinsic QRS undergoing electroanatomic mapping (EAM)-guided HBP. HBP was attempted in 43 patients. In 28 cases with narrow QRS, the EnSite AutoMap Module was used for automated assessment of the QRS morphology resulting from pace mapping in the His cloud area with either a diagnostic catheter or the His lead. An intrinsic morphology match score (IMS) was calculated for 1.546 QRS complexes and assessed regarding its accuracy and performance in classifying the individual pacing response as either selective HBP (S-HBP), nonselective HBP (NS-HBP) or right ventricular stimulation. Automated morphology comparison of 354 intrinsic beats with the individual reference determined a test accuracy of 99% (95% CI 98.96–99.04) and a precision of 97.99–99.5%. For His-lead stimulation, an IMS ≥ 89% identified S-HBP with a sensitivity, specificity and positive predictive value of 1.00 (0.99, 1.00) and a negative predictive value of 0.99 (0.98, 1.00). An IMS between 78 and < 89% indicated NS-HBP with a sensitivity and specificity of 1.00 (0.99, 1.00) and 0.99 (0.98, 1.00), respectively. IMS represents a new automated measure for standardized individual morphology classification in patients with normal QRS undergoing EAM-guided HBP. Clinical trial registration: NCT04416958.
CRIS-Team Scopus Importer:2022-03-18

Impact of Eligibility Criteria on Clinical Outcomes of Firehawk and XIENCE Coronary Drug-Eluting Stent in an All-Comers Randomized Trial - Saito, Yuichi; Wijns, William; Baumbach, Andreas; Xu, Bo; Kelbaek, Henning; Van Royen, Niels; Zheng, Ming; Knaapen, Paul; Slagboom, Ton; Johnson, Tom; Vlachojannis, Georgios; Holmvang, Lene; et al. (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Interventional treatment and outcome in elderly patients with stable coronary artery disease. Results from the German ALKK registry - Rittger, Harald; Hochadel, M.; Behrens, S.; Hauptmann, K. E.; Zahn, R.; Mudra, H.; Brachmann, J.; Zeymer, U. (Herz, 2014)
The number of elderly and very elderly patients undergoing percutaneous coronary interventions (PCI) is increasing. We therefore analyzed data from the German ALKK registry (Arbeitsgemeinschaft Leitende Krankenhausärzte; Working Group of Hospital Cardiologists) to determine differences in procedural features, antithrombotic treatment, and in-hospital outcome in patients with coronary artery disease (CAD) according to age in a large series of patients.The present analysis was based on the data of 35,534 consecutive patients undergoing elective PCI who were enrolled in the ALKK registry. Of these 27,145 (76.4 %) were younger than 75 years, 7,645 (21.5 %) were aged between 75 and 84 years, and 744 (2.1 %) patients were older than 85 years. Mean age was 68.5 years (60.9-74.5 years), and 25,784 patients (72.6 %) were male. Overall intraprocedural events were very low (1.1 %) and there was no significant difference between the three age groups [< 75 years (1.1 %); 75-< 85 years (1.2 %); >= 85 years (0.5 %) (p = not significant)]. Rates of in-hospital death, stroke and transient ischemic attack (TIA), as well as the combined endpoint in-hospital major adverse cardiac and cerebrovascular events (MACCE) were also very low (0.6 % vs. 0.9 % vs. 0.9 %; p < 0.001) but significantly higher in elderly patients with no further increase in the very elderly patient group.We found no differences in this registry in intraprocedural complications during elective PCI between younger and elderly patients. Although in-hospital MACCE were somewhat higher in the elderly, the overall event rate was low and thus elderly patients should not be deprived from this therapy because of age alone.
EVALuna2:12017

Leitlinie zum Einrichten und Betreiben von Herzkatheterlaboren und Hybridoperationssälen/Hybridlaboren: 3. Auflage 2015 - Schächinger, V.; Nef, H.; Achenbach, Susanne; Butter, C.; Deisenhofer, I.; Eckardt, L.; Eggebrecht, H.; Kuon, E.; Levenson, B.; Linke, A.; Madlener, K.; Mudra, H.; et al. (Der Kardiologe, 2015)
Besides diagnostic heart catheterization and coronary interventions, numerous additional procedures are now performed in catheterization laboratories with special requirements for equipment and sequence of operations. The current third edition of the guidelines to establish and operate catheterization laboratories, hybrid operating rooms (OR) and hybrid laboratories gives recommendations with respect to these procedures, including invasive electrophysiology, implantation of rhythm devices and also with respect to catheter-based valve therapy, especially transcather aortic valve implantation (TAVI). Special aspects of hygiene and structural conditions, which are required for hybrid ORs and hybrid laboratories, are discussed. The guidelines provide recommendations for planning a catheterization laboratory and hybrid OR as well as for operational aspects, which include legal regulations, hygiene requirements, structural architectural aspects and radiation safety. Furthermore, aspects of technical equipment, integration of modern three-dimensional imaging modalities, data management and workforce, including cardiac analgesia, are provided.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac catheterization; Coronary intervention; Electrophysiology; Hybrid operating room; Transcatheter aortic valve implantation

Long-Term Outcomes After Treatment With a Paclitaxel-Coated Balloon Versus Balloon Angioplasty: Insights From the PEPCAD-DES Study (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent Please Paclitaxel-Coated Percutaneous Transluminal C - Rittger, Harald; Waliszewski, Matthias; Brachmann, Johannes; Hohenforst-Schmidt, Wolfgang; Ohlow, Marc; Brugger, Andreas; Thiele, Holger; Birkemeyer, Ralf; Kurowski, Volkhard; Schlundt, Christian; Zimmermann, Stefan; Lonke, Sandra; et al. (Jacc-Cardiovascular Interventions, 2015)
The intention this PEPCAD-DES (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent Please Paclitaxel Eluting Percutaneous Transluminal Coronary Angioplasty [PTCA] Catheter) study update was to demonstrate the safety and efficacy of paclitaxel-coated balloon (PCB) angioplasty in patients with DES-ISR at 3 years.In the PEPCAD-DES trial late lumen loss and the need for repeat target lesion revascularization (TLR) was significantly reduced with PCB angioplasty compared with plain old balloon angioplasty (POBA) in patients with drug-eluting stent in-stent restenosis (DES-ISR) at 6 months. We evaluated whether the clinical benefit of reduced TLR and major adverse cardiac events (MACE) was maintained up to 3 years.A total of 110 patients with DES-ISR in native coronary arteries with reference diameters ranging from 2.5 mm to 3.5 mm and lesion lengths <=22 mm were randomized to treatment with either PCB or POBA in a multicenter, randomized, single-blind clinical study. With a 2:1 randomization, 72 patients were randomized to the PCB group and 38 patients to the POBA group. At baseline, there were lesions with at least 2 stent layers in PCB (52.8%, 38 of 72) and POBA (55.3%, 21 of 38) patients.At 36 months, the TLR rates were significantly lower in the PCB group compared with the POBA control group (19.4% vs. 36.8%; p = 0.046). Multiple TLRs in individual patients were more frequent in the POBA group compared with the PCB group (more than 1 TLR: POBA, 13.2%; PCB, 1.4%; p = 0.021). The 36-month MACE rate was significantly reduced in the PCB group compared with the POBA group (20.8% vs. 52.6%, log-rank p = 0.001).PCB angioplasty was superior to POBA for the treatment of DES-ISR patients in terms of MACE and TLR for up to 36 months. There was no late catch-up phenomenon. (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent® Please Paclitaxel Eluting Percutaneous Transluminal Coronary Angioplasty [PTCA] Catheter [PEPCAD-DES]; NCT00998439).
EVALuna2:12089

MEMS Technology in Cardiology: Advancements and Applications in Heart Failure Management Focusing on the CardioMEMS Device - Ciotola, Francesco; Pyxaras, Stylianos; Rittger, Harald; Buia, Veronica (Sensors, 2024)
Heart failure (HF) is a complex clinical syndrome associated with significant morbidity, mortality, and healthcare costs. It is characterized by various structural and/or functional abnormalities of the heart, resulting in elevated intracardiac pressure and/or inadequate cardiac output at rest and/or during exercise. These dysfunctions can originate from a variety of conditions, including coronary artery disease, hypertension, cardiomyopathies, heart valve disorders, arrhythmias, and other lifestyle or systemic factors. Identifying the underlying cause is crucial for detecting reversible or treatable forms of HF. Recent epidemiological studies indicate that there has not been an increase in the incidence of the disease. Instead, patients seem to experience a chronic trajectory marked by frequent hospitalizations and stagnant mortality rates. Managing these patients requires a multidisciplinary approach that focuses on preventing disease progression, controlling symptoms, and preventing acute decompensations. In the outpatient setting, patient self-care plays a vital role in achieving these goals. This involves implementing necessary lifestyle changes and promptly recognizing symptoms/signs such as dyspnea, lower limb edema, or unexpected weight gain over a few days, to alert the healthcare team for evaluation of medication adjustments. Traditional methods of HF monitoring, such as symptom assessment and periodic clinic visits, may not capture subtle changes in hemodynamics. Sensor-based technologies offer a promising solution for remote monitoring of HF patients, enabling early detection of fluid overload and optimization of medical therapy. In this review, we provide an overview of the CardioMEMS device, a novel sensor-based system for pulmonary artery pressure monitoring in HF patients. We discuss the technical aspects, clinical evidence, and future directions of CardioMEMS in HF management.
CRIS-Team Scopus Importer:2024-05-24
Keywords: CardioMEMS; congestive heart failure (CHF); microelectromechanical sensors; pulmonary artery hypertension (PAH); remote monitoring; telemedicine

Mild therapeutic hypothermia after out-of-hospital cardiac arrest complicating ST-elevation myocardial infarction: Long-term results in clinical practice - Zimmermann, Stefan; Flachskampf, Frank A.; Schneider, Reinhard; Dechant, Katharina; Alff, Anna; Klinghammer, Lutz; Rittger, Harald; Achenbach, Stephan (Clinical Cardiology, 2013)
Background Recently, mild therapeutic hypothermia (MTH) has been integrated into the European resuscitation guidelines to improve outcomes after out-of-hospital cardiac arrest (OHCA). Data on long-term results are limited, especially in patients with acute ST-elevation myocardial infarction (STEMI). Hypothesis Invasive MTH influences long-term prognosis after OHCA due to STEMI. Methods We analyzed 48 patients who underwent emergency coronary angiography for STEMI after witnessed OHCA. In 24 consecutive patients, MTH was performed via intravascular cooling (CoolGard System, 34°C maintained for 24 hours) after initialization by rapid infusion of cold saline. Clinical, procedural, and mortality data were compared to 24 historical controls. Neurological recovery was assessed using the Cerebral Performance Category score (CPC) at 30-day and 1-year follow-up. Results Median time delay until arrival of emergency medical service was 6 minutes (MTH group) vs 6.5 minutes (controls) (P = 0.16). Initial rhythm was ventricular fibrillation in 75% vs 66.7% (P = 0.75). There were no differences regarding baseline characteristics, angiographic findings, and success of cardiac catheterization procedures. MTH was not associated with a higher frequency of bleeding complications or of pneumonia. Thirty-day mortality was 33.3% in both groups. One-year mortality was 37.5% (MTH group) vs 50% (controls) (P = 0.56). At 1 year, favorable neurological outcome (CPC ≤2) was significantly more frequent in the MTH group (58.3% vs 20.8%, P = 0.017). Multivariate analysis identified MTH as independent predictor of favorable neurological outcome (P < 0.02, odds ratio: 12.73). Conclusions MTH via intravascular cooling improves neurological long-term prognosis after OHCA due to STEMI and is safe in clinical practice. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-08

Minielectrode catheter technology for near zero-fluoroscopy substrate-guided ablation of typical atrial flutter - Betz, Johanna; Vitali-Serdoz, Laura; Buia, Veronica; Walaschek, Janusch; Rittger, Harald; Bastian, Dirk (Heart Rhythm O2, 2021)
Background: MicroFidelity catheter technology may facilitate voltage-guided ablation by high-resolution electroanatomic mapping (HR-EAM) and precisely targeted energy application. Objective: To evaluate the performance of minielectrode (ME) technology for zero-fluoroscopy substrate-guided cavotricuspid isthmus (CTI) ablation. Methods: Eighty-two patients underwent near zero-fluoroscopy substrate-guided CTI ablation using a nonirrigated large-tip catheter with 3 MEs. The CTI was subdivided into 15 electroanatomic segments. Bipolar voltage maps were compared with ME signals. The outcome was compared with a historic cohort of 92 patients who underwent linear ablation. Results: Compared with linear ablation, the substrate-guided approach was associated with an almost halved ablation duration (336 ± 228 vs 649 ± 409 seconds, P < .001), halved radiofrequency energy applied (14.2 ± 10.6 vs 28.6 ± 19.6 kJ, P < .001), and shorter procedure duration (60.8 ± 33.8 vs 76.3 ± 40.9 minutes, P = .008) limiting the extent of energy delivery to 22.7% of the CTI area. HR-EAM visualized 2.03 ± 0.88 conductive pathways with a diameter of 5.35 ± 1.98 mm. A higher number of ME-detected bundles and a larger channel diameter correlated with increased ablation requirements. In 97.6% of the voltage-guided and 88.0% of the linear procedures, fluoroscopy was not used. Conclusion: HR-EAM-based substrate-guided CTI ablation may improve procedural outcome compared with the linear approach. Enhanced identification of discrete conductive pathways correlates with ablation efficacy. The electroanatomic subdivision of the CTI into 15 segments was feasible and may improve the understanding and comparability of anatomic variants and ablation results. Independent of the ablation strategy, modern EAM technology enables safe zero-fluoroscopy procedures in the majority of cases.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Atrial flutter; Catheter ablation; Electroanatomic mapping; Maximum voltage-guided; Zero fluoroscopy

Perioperative sensor and algorithm programming in patients with implanted icds and pacemakers for cardiac resynchronization therapy - Niedermeier, Alexander; Vitali-Serdoz, Laura; Fischlein, Theodor; Kirste, Wolfgang; Buia, Veronica; Walaschek, Janusch; Rittger, Harald; Bastian, Dirk (Sensors, 2021)
Background: ICDs and pacemakers for cardiac resynchronization therapy (CRT) are complex devices with different sensors and automatic algorithms implanted in patients with advanced cardiac diseases. Data on the perioperative management and outcome of CRT carriers undergoing surgery unrelated to the device are scarce. Methods: Data from 198 CRT device carriers (100 with active rate responsive sensor) were evaluated regarding perioperative adverse (device-related) events (A(D)E) and lead parameter changes. Results: Thirty-nine adverse observations were documented in 180 patients during preoperative interrogation, which were most often related to the left-ventricular lead and requiring intervention/reprogramming in 22 cases (12%). Anesthesia-related events occurred in 69 patients. There was no ADE for non-cardiac surgery and in pacemaker-dependent patients not programmed to an asynchronous pacing mode. Post-operative device interrogation showed significant lead parameter changes in 64/179 patients (36%) requiring reprogramming in 29 cases (16%). Conclusion: The left-ventricular pacing lead represents the most vulnerable system component. Comprehensive pre and post-interventional device interrogation is mandatory to ensure proper system function. The type of ICD function suspension has no impact on each patient’s outcome. Precautionary activity sensor deactivation is not required for non-cardiac interventions. Routine prophylactic device reprogramming to asynchronous pacing appears inessential. Most of the CRT pacemakers do not require surgery-related reprogramming.
CRIS-Team Scopus Importer:2021-12-31
Keywords: Cardiac resynchronization therapy; Defibrillator shock; Electromagnetic interference; Heart failure; ICD; Implantable cardioverter defibrillator; Sensors; Sudden cardiac death

Successful Management of Iatrogenic Left Main Grade III Perforation With Coil Embolization - Ciotola, Francesco; Rittger, Harald; Pyxaras, Stylianos (Jacc-Cardiovascular Interventions, 2023)
CRIS-Team Scopus Importer:2024-12-16
Keywords: coiling; coronary perforation; left main intervention

Transcatheter closure of ruptured sinus of Valsalva aneurysm into the right ventricle with an Amplatzer Vascular Plug II - Rittger, Harald; Gundlach, Ulrike; Koch, Andreas (Catheterization and Cardiovascular Interventions, 2015)
We report a case of a 52-year-old female patient with perforated sinus of Valsalva (SVA) aneurysm presenting with severe left-to-right shunt from the aorta into the right ventricle.Aneuryms of the aortic sinus, better known as SVA are rare. Until interventional devices were introduced, the only treatment option for ruptured SVA aneurysms was surgery.The case was discussed in the heart team and decision was made to implant an Amplatzer Vascular Plug (AVP) II. Initially, closing attempts using AVP 16 mm and 14 mm devices were performed. Presumably as a consequence of inadequate sizing, the discs were not well formed in the connecting tunnel, leaving a severe rest shunt after both procedures. Finally, after implantation of a 12 mm AVP-device, only a minimal rest shunt remained detectable. Absence of aortic regurgitation was confirmed by transesophageal echocardiography, and the occluder was released. Mean pulmonary artery pressure immediately decreased from 39 to 15 mm Hg. Medication with aspirin (100 mg qid) and clopidogrel (75 mg qid) was initiated. Follow-up examinations at 4 weeks and 3 months confirmed the minimal rest shunt and a continuous decrease of systolic pulmonary artery pressure to 35 mm Hg, as assessed with transthoracal echocardiography.In conclusion, in cases of SVA rupture, closure with an AVP II represents an alternative to surgical treatment and other devices used for transcatheter treatment of SVA. © 2014 Wiley Periodicals, Inc.
EVALuna2:12010

Transtracheal single-point stent fixation in posttracheotomy tracheomalacia under cone-beam computer tomography guidance by transmural suturing with the Berci needle - a perspective on a new tool to avoid stent migration of Dumon stents - Hohenforst-Schmidt, Wolfgang; Linsmeier, Bernd; Zarogoulidis, Paul; Freitag, Lutz; Darwiche, Kaid; Browning, Robert; Turner, J. Francis; Huang, Haidong; Li, Qiang; Vogl, Thomas; Zarogoulidis, Konstantinos; Brachmann, Johannes; et al. (Therapeutics and Clinical Risk Management, 2015)
Tracheomalacia or tracheobronchomalacia (TM or TBM) is a common problem especially for elderly patients often unfit for surgical techniques. Several surgical or minimally invasive techniques have already been described. Stenting is one option but in general long-time stenting is accompanied by a high complication rate. Stent removal is more difficult in case of self-expandable nitinol stents or metallic stents in general in comparison to silicone stents. The main disadvantage of silicone stents in comparison to uncovered metallic stents is migration and plugging. We compared the operation time and in particular the duration of a sufficient Dumon stent fixation with different techniques in a patient with severe posttracheotomy TM and strongly reduced mobility of the vocal cords due to Parkinson's disease. The combined approach with simultaneous Dumon stenting and endoluminal transtracheal externalized suture under cone-beam computer tomography guidance with the Berci needle was by far the fastest approach compared to a (not performed) surgical intervention, or even purely endoluminal suturing through the rigid bronchoscope. The duration of the endoluminal transtracheal externalized suture was between 5 minutes and 9 minutes with the Berci needle; the pure endoluminal approach needed 51 minutes. The alternative of tracheobronchoplasty was refused by the patient. In general, 180 minutes for this surgical approach is calculated. The costs of the different approaches are supposed to vary widely due to the fact that in Germany 1 minute in an operation room costs on average approximately 50-60EUR inclusive of taxes. In our own hospital (tertiary level), it is nearly 30EUR per minute in an operation room for a surgical approach. Calculating an additional 15 minutes for patient preparation and transfer to wake-up room, therefore a total duration inside the investigation room of 30 minutes, the cost per flexible bronchoscopy is per minute on average less than 6EUR. Although the Dumon stenting requires a set-up with more expensive anesthesiology accompaniment, which takes longer than a flexible investigation estimated at 1 hour in an operation room, still without calculation of the costs of the materials and specialized staff that the surgical approach would consume at least 3,000EUR more than a minimally invasive approach performed with the Berci needle. This difference is due to the longer time of the surgical intervention which is calculated at approximately 180 minutes in comparison to the achieved non-surgical approach of 60 minutes in the operation suite.
EVALuna2:12091

Use of coronary physiology to guide revascularization in clinical practice: results of the F(FR)2 registry - Altstidl, Johannes Michael; Achenbach, Stephan; Feyrer, Johannes; Nazli, J. Benedikt; Marwan, Mohamed; Gaede, Luise; Möllmann, Helge; Giesler, Tom; Rittger, Harald; Pauschinger, Matthias; Rudolph, Tanja K.; Moshage, Werner; et al. (Clinical Research in Cardiology, 2024)
Background: Despite the recommendation of coronary physiology to guide revascularization in angiographically intermediate stenoses without established correlation to ischemia, its uptake in clinical practice is slow. Aims: This study aimed to analyze the use of coronary physiology in clinical practice. Methods: Based on a multicenter registry (Fractional Flow Reserve Fax Registry, F(FR)2, ClinicalTrials.gov identifier NCT03055910), clinical use, consequences, and complications of coronary physiology were systematically analyzed. Results: F(FR)2 enrolled 2,000 patients with 3,378 intracoronary pressure measurements. Most measurements (96.8%) were performed in angiographically intermediate stenoses. Out of 3,238 lesions in which coronary physiology was used to guide revascularization, revascularization was deferred in 2,643 (78.2%) cases. Fractional flow reserve (FFR) was the most common pressure index used (87.6%), with hyperemia induced by an intracoronary bolus of adenosine in 2,556 lesions (86.4%) and intravenous adenosine used for 384 measurements (13.0%). The route of adenosine administration did not influence FFR results (change-in-estimate -3.1% for regression model predicting FFR from diameter stenosis). Agreement with the subsequent revascularization decision was 93.4% for intravenous and 95.0% for intracoronary adenosine (p = 0.261). Coronary artery occlusion caused by the pressure wire was reported in two cases (0.1%) and dissection in three cases (0.2%), which was fatal once (0.1%). Conclusions: In clinical practice, intracoronary pressure measurements are mostly used to guide revascularization decisions in angiographically intermediate stenoses. Intracoronary and intravenous administration of adenosine seem equally suited. While the rate of serious complications of wire-based intracoronary pressure measurements in clinical practice seems to be low, it is not negligible. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-06-14
Keywords: Complications; Coronary artery disease; Coronary physiology; Fractional flow reserve (FFR); Registry